Analisis Kesalahan Kalimat dalam Teks Opini dengan Tema Sosial pada Website Tirto Edisi Februari 2025 sebagai Upaya Pembelajaran Bahasa dan Sastra untuk Meningkatkan Kemampuan Berpikir Kritis Siswa - Rafa Naufal Anoka; Zidan Muhammad Zamzami; Heru Wicaksono; Muhammad Rakha Jidane Setiawan; Asep Purwo Yudi Utomo; Ermawati Ermawati; Arum Yuliya Lestari (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2025)
The proper use of language in opinion texts plays a crucial role in constructing clear and convincing arguments. However, various sentence errors are still found in opinion texts, which can hinder readers' comprehension. This study aims to analyze sentence errors in social-themed opinion texts published on the Tirto website in February 2025 and evaluate their implications for language and literature learning to enhance students' critical thinking skills. The research method used is qualitative descriptive analysis with a linguistic approach. Data were collected through documentation techniques and analyzed using syntactic theory. The study results show that the most dominant errors include improper conjunction usage, ineffective clause structures, as well as spelling and punctuation mistakes. These errors have the potential to cause ambiguity and weaken the quality of argumentation in opinion texts. These findings indicate that error analysis can be used as teaching material in language and literature learning to improve students' critical thinking abilities. Therefore, this study recommends integrating syntactic analysis and opinion text analysis into language learning to develop better language skills.